2003
DOI: 10.1309/vh1kmv8wb7gb7r14
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Instrument-Driven Reflex Manual Differential Leukocyte Counts

Abstract: Automated peripheral blood leukocyte differential counts (LDCs) are widely accepted in routine practice. However, many laboratories still reflexively perform manual LDCs based solely on abnormal automated results or instrument "flags," before any manual triage step. We describe our transition to a procedure that uses manual methods to validate, rather than to replace, automated LDCs (an approach recommended early in the development of automated methods, but still not used in many clinical laboratories). Manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Lantis et al showed that laboratory operations could be optimised by modifying the algorithm for performing leukocyte differentials [13]. Instead of establishing criteria for manual differentiation, the authors proposed criteria for blood smear review.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lantis et al showed that laboratory operations could be optimised by modifying the algorithm for performing leukocyte differentials [13]. Instead of establishing criteria for manual differentiation, the authors proposed criteria for blood smear review.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of establishing criteria for manual differentiation, the authors proposed criteria for blood smear review. Based on the results of blood smear review, manual differentials are performed or the automated differential is reported [13]. In veterinary medicine, experts’ opinions about blood smear reviews are diverse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations